2021
DOI: 10.3174/ajnr.a7193
|View full text |Cite
|
Sign up to set email alerts
|

When Should a Brain MRI Be Performed in Children with New-Onset Seizures? Results of a Large Prospective Trial

Abstract: BACKGROUND AND PURPOSE:There is a paucity of data regarding the incidence of structural brain lesions in children with new-onset unprovoked seizures. Our aim was to determine the frequencies and types of epileptogenic lesions detected on a dedicated epilepsy protocol MR imaging according to age group, the presence of developmental delay, and the number and types of seizures. MATERIALS AND METHODS:Consecutive children between 6 months and 18 years of age with new-onset unprovoked seizures were included. The fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
2
3
0
Order By: Relevance
“…This rate of identification is higher in infants compared to the wider focal pediatric epilepsy population, in whom we previously reported that 46% of children (age 1 month to 17 years) with focal seizures had identified etiology 10 . In the current study, we found that structural abnormalities were the most common cause, emphasizing the need for high‐quality neuroimaging in infantile‐onset focal epilepsy 13–15 . Our detected rate of known etiologies is similar to a recent population‐based study from Sweden, 4 which enrolled all infants with epilepsy presenting in the first 2 years of life and found a known etiology in 59% (including structural in 34%, genetic in 15%, and metabolic in 8.6%).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This rate of identification is higher in infants compared to the wider focal pediatric epilepsy population, in whom we previously reported that 46% of children (age 1 month to 17 years) with focal seizures had identified etiology 10 . In the current study, we found that structural abnormalities were the most common cause, emphasizing the need for high‐quality neuroimaging in infantile‐onset focal epilepsy 13–15 . Our detected rate of known etiologies is similar to a recent population‐based study from Sweden, 4 which enrolled all infants with epilepsy presenting in the first 2 years of life and found a known etiology in 59% (including structural in 34%, genetic in 15%, and metabolic in 8.6%).…”
Section: Discussionsupporting
confidence: 86%
“…10 In the current study, we found that structural abnormalities were the most common cause, emphasizing the need for high-quality neuroimaging in infantile-onset focal epilepsy. [13][14][15] Our detected rate of known etiologies is similar to a recent population-based study from Sweden, 4 which enrolled all infants with epilepsy presenting in the first 2 years of life and found a known etiology in 59% (including structural in 34%, genetic in 15%, and metabolic in 8.6%). The rate of structural etiologies in our cohort was higher (52%), likely because we included only those with focal-onset seizures.…”
Section: Discussionsupporting
confidence: 84%
“…MR imaging of the brain should be performed in any child with unprovoked, newly developed seizures [7,8,9,10,11]. According to the ILAE, conditions that can cause a seizure also include, but are not limited to: pre -and perinatal trauma and stroke [12]. The described patient likely developed epilepsy on the background of a history of hemorrhagic stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance imaging (MRI) of the brain should be performed in any child with unprovoked, new-onset seizures, especially if sedation is not required. The International League Against Epilepsy emphasizes the need to consider etiology at every stage of diagnosis, including structural etiology, which is best assessed by brain MRI to help classify a possible epileptic syndrome [11]. Obtaining a negative image on MRI is an indication for single-photon emission computed tomography (SPECT) imaging, which is also helpful in identifying an epileptogenic focus before performing surgery to treat drugresistant epilepsy [12][13].…”
Section: Brief Description Of the State Of Knowledgementioning
confidence: 99%